2001
DOI: 10.1182/blood.v98.13.3871
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal-onset hereditary coproporphyria with male pseudohermaphrodism

Abstract: The appearance of hereditary coproporphyria (HCP) before puberty is very rare, and all reported cases of early-onset HCP have been in the homozygous or the compound heterozygous state. Some have been identified as harderoporphyria, which is a rare erythropoietic variant form of HCP. These conditions can be differentiated by molecular analysis because the gene abnormality responsible for harderoporphyria seems to be unique (K404E IntroductionHereditary coproporphyria (HCP) is a hereditary autosomaldominant dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…These results are consistent with HCP, but not harderoporphyria. Similar to our patient, another neonatal patient with HCP showed neonatal jaundice and hemolytic anemia with a (Table 3) (Takeuchi et al 2001). This case also did not have a mutation that is found in patients with harderoporphyria and the coproporphyrin III level in the feces was greatly increased.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These results are consistent with HCP, but not harderoporphyria. Similar to our patient, another neonatal patient with HCP showed neonatal jaundice and hemolytic anemia with a (Table 3) (Takeuchi et al 2001). This case also did not have a mutation that is found in patients with harderoporphyria and the coproporphyrin III level in the feces was greatly increased.…”
Section: Discussionsupporting
confidence: 86%
“…Hypospadias and adrenocortical insufficiency were observed in our patient and in the previously reported neonatal patient with HCP (Table 3) (Takeuchi et al 2001). In patients with harderoporphyria and compound heterozygous mutations of p.Lys404Glu and IVS6 + 3A>G (Lamoril et al 1998), which result in exon 6 skipping at the mRNA level, only hypospadias was observed.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations